PENGGUNAAN STRATEGITHINK-TALK-WRITE (TTW) UNTUK MENINGKATKAN HASIL BELAJAR FISIKASISWA KELAS XII IPA 1 SMA NEGERI 1 SALO TAHUN PELAJARAN 2015/2016: Use of Think-Talk-Write (TTW) Strategy to Increase LearningOutcome on Physics Subjact XII IPA 1 SMANegeri 1 Salo at the Year 2015/2016 - ZULBAKRI ZULBAKRI (UIR Press, 2017)
Classroom action research has been done in SMA Negeri 1 Salo on Physics subject with researchobject of XII IPA 1 student in odd semester 2015/2016. This study was conducted as an effort toimprove the learning result of Physics on the subject of money and banking for the students of gradeXII IPA 1. Think-Talk-Write (TTW) learning model is chosen to be applied after the observation andreflection done by the researcher. Researchers plan actions based on observations and reflections thathave been made through the preparation of Think-Talk-Write (TTW) learning-based learning toolsconsisting of test questions, observation sheets and lesson plans and other supporting learning tools.The Think-Talk-Write (TTW) learning model convinces students to do 4 activities: write solutions to agiven problem or question, organize all the work step by step, correct all jobs so that no jobs are leftout, and believe that their best work That is complete, easy to read and guaranteed authenticity. Thisstudy can be completed in 2 cycles of 6 meetings and formative tests conducted at each end of the cycle.The result of the research is the observation and recapitulation data of the result and the recapitulationof learning completeness showed that there has been an increase of positive student learning activity inclass and the increase of test mean and the increase of classical completeness from cycle 1 to cycle 2.The average value in cycle 1 is 50% enough). The average value in cycle 2 is 77% (good). Studentactivity during the learning process is observed by the observer as data for evaluation and reflection.The average recapitulation of test and learning completeness is obtained from the test scoresperformed at the end of each meeting. Based on the research result, it can be concluded that theimplementation of Think-Talk-Write (TTW) strategy in class XII IPA 1 SMA Negeri 1 Salo can improvethe learning result of Physics subject which is shown by the average of classical test and completenessin every cycle.